2008
DOI: 10.1186/1471-2350-9-30
|View full text |Cite
|
Sign up to set email alerts
|

Gene polymorphisms of superoxide dismutases and catalase in diabetes mellitus

Abstract: Background: Reactive oxygen species generated by hyperglycaemia modify structure and function of lipids, proteins and other molecules taking part in chronic vascular changes in diabetes mellitus (DM). Low activity of scavenger enzymes has been observed in patients with DM. Protective role of scavenger enzymes may be deteriorated by oxidative stress. This study was undertaken to investigate the association between gene polymorphisms of selected antioxidant enzymes and vascular complications of DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
0
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(113 citation statements)
references
References 35 publications
(33 reference statements)
6
97
0
10
Order By: Relevance
“…It must be noted that previous studies did not find an association with CAT and T1DM [28,29]. CAT has been shown to be associated with several other disease conditions.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…It must be noted that previous studies did not find an association with CAT and T1DM [28,29]. CAT has been shown to be associated with several other disease conditions.…”
Section: Discussionmentioning
confidence: 73%
“…When a genetically engineered derivative of the peroxisomal antioxidant enzyme catalase (CAT-SKL), induced by intracerebroventricular injection of Aβ [25][26][27][28][29][30][31][32][33][34][35] in the mature rat brain, it is able to reduce the toxicity of the accumulated beta-amyloid in the brain [44]. Free radical mediated oxidative stress have long been considered to be involved in the pathogenesis of diabetic complications but could they also because protein aberrations and some pathology in cells [45].…”
Section: Discussionmentioning
confidence: 99%
“…A case-control study indicated that homozygosity for the SOD2 rs4880 Val allele is associated with an increased risk of DN, thus supporting the hypothesis that oxidative stress contributes to this severe long-term complication in diabetic patients (Môllsten et al, 2007). Other studies showed that oxidative stress in DM1 and DM2 can be accelerated not only due to increased ROS production caused by hyperglycemia, but also by the reduced ability of the antioxidant defense system caused at least partly by deleterious SNPs of some scavenger enzymes (Flekac et al, 2008). The presence of the TT (Val/Val) homozygous genotype of the SOD2 gene was associated with poorer diabetes control in comparison with CT (Ala/Val) and CC (Ala/Ala) genotypes.…”
Section: Antioxidant Enzymes: Superoxide Dismutase (Sod) and Catalasementioning
confidence: 88%
“…17 Moreover, several single nucleotide polymorphisms (SNPs) in the CAT gene have been found to be associated with diabetic nephropathy and neuropathy. 18,19 However, it is unknown whether there is an association between antioxidant gene polymorphisms and clinical outcomes of acute kidney injury (AKI). Therefore, in the current study, we studied the association between MnSOD, CAT and GPX1 gene polymorphisms and clinical outcomes of AKI.…”
Section: Introductionmentioning
confidence: 99%